Gender and Colonialism - Moane, Geraldine. author. aut Link
XI, 272 p.
Keywords: Drawing on the writings of diverse authors, including Jean Baker Miller, Bell Hooks, Mary Daly, Frantz Fanon, Paulo Freire and Ignacio Martin-Baro, as well as on women's experiences, this book aims to develop a 'liberation psychology'; which would aid in transforming the damaging psychological patterns associated with oppression and taking action to bring about social change. The book makes systematic links between social conditions and psychological patterns, and identifies processes such as building strengths, cultivating creativity, and developing solidarity.